2020
DOI: 10.1177/1747519820966985
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diaryl sulfides based on copper-doped OMS-2

Abstract: We describe a practical protocol for efficiently preparing diaryl sulfide compounds using Cu–OMS-2 as the catalyst. Cu–OMS-2 originates from manganese oxide octahedral molecular sieves modified with copper ions and catalyzes the C–S coupling reaction of substituted thiophenols and aryl halides. This protocol has the advantages of environmental friendliness, simple operation, high yields, good tolerance of functional groups, and the Cu–OMS-2 catalytic material can be recycled several times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Liu et al 31 found that the optimal CuO/OMS-2 catalyst provides reactivity with a T 90 of 55 °C and the interaction between the highly dispersed CuO and OMS-2 support generates active sites for CO oxidation. Yu et al 32 also reported a practical protocol for efficiently preparing diaryl sulfides using Cu-OMS-2 to catalyze the C–S coupling reactions of substituted thiophenols and aryl halides. Recently, Han et al 33 reported that both the catalytic performance for mercury removal and the sulfur resistance ability could be improved by modification of OMS-2 using copper.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 31 found that the optimal CuO/OMS-2 catalyst provides reactivity with a T 90 of 55 °C and the interaction between the highly dispersed CuO and OMS-2 support generates active sites for CO oxidation. Yu et al 32 also reported a practical protocol for efficiently preparing diaryl sulfides using Cu-OMS-2 to catalyze the C–S coupling reactions of substituted thiophenols and aryl halides. Recently, Han et al 33 reported that both the catalytic performance for mercury removal and the sulfur resistance ability could be improved by modification of OMS-2 using copper.…”
Section: Introductionmentioning
confidence: 99%